2009
DOI: 10.1038/ejhg.2008.263
|View full text |Cite
|
Sign up to set email alerts
|

The complex interaction between APOE promoter and AD: an Italian case–control study

Abstract: The single nucleotide polymorphisms (SNPs) rs449647, rs769446 and rs405509 in the promoter region of the APOE gene have been variously suggested to be e4-independent risk factors for Alzheimer's disease (AD). A previous Italian study found that the rs449647 was significantly associated with late-onset AD. The aim of this study was to verify whether these APOE promoter SNPs are genetic risk factors for AD and to investigate their interaction with the common APOE polymorphism. A total of 169 clinically diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…The frequencies of APOE genotypic and allelic frequencies analyzed here were similar to those reported in other samples [15,19,31]. Our results did not show associations between cognitive performance and any of APOE polymorphisms analyzed here, except for rs429358.…”
Section: Discussionsupporting
confidence: 90%
“…The frequencies of APOE genotypic and allelic frequencies analyzed here were similar to those reported in other samples [15,19,31]. Our results did not show associations between cognitive performance and any of APOE polymorphisms analyzed here, except for rs429358.…”
Section: Discussionsupporting
confidence: 90%
“…The apoE4/E4 proinflammatory genotype was present in 2.9 per cent of the Tsimane sample whereas the at-risk genotype (GG) of the SNP in the promoter region (rs405509), which has also been associated with Alzheimer’s disease (Bizzarro et al 2009), was found in 6.4 per cent of the Tsimane (see Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…A more recent study reported both TT and GG genotypes of rs405509 with higher odds ratios for AD compared with the GT group in the APOE ɛ4 carriers. However, in ɛ3/ɛ3 carriers, both TT and GG showed lower frequencies than GT in patients with AD . In another study, the rs405509 T‐APOEɛ4 haplotype could increase the risk of AD .…”
Section: Introductionmentioning
confidence: 90%